Thermo-elastic-viscoplastic-damage model for self-heating and mechanical behavior of thermoplastic polymers. (October 2019) - Shen, Fei; Kang, Guozheng; Lam, Yee Cheong; Liu, Yujie; Zhou, Kun
Abstract: A thermo-elastic-viscoplastic-damage model based on thermodynamics is developed to describe the self-heating and stress-strain behavior of thermoplastic polymers under tensile loading. The constitutive model considers temperature-dependent elasticity, nonlinear viscoplastic flow and damage evolution. The model includes the important self-heating of a polymer caused by the viscoplasticity and the often neglected damage energy dissipation during deformation. The model parameters are calibrated from the monotonic and repeated loading tests for polyamide 6 under different temperatures and loading rates. In particular, the damage evolution is evaluated by the stiffness reduction in the repeated loading tests. The proposed model is implemented in a finite element package to predict the self-heating and mechanical behavior of the polymer at a high loading rate. The predicted temperature and load evolution curves agree with the experimental data. Highlights: A thermo-elastic-viscoplastic-damage model is developed for thermoplastics. Coupling relationship among mechanical behavior, damage and temperature is considered. Dissipated energies in damage and viscoplastic flow are considered for self-heating. Damage evolution under different temperatures is studied through repeated loading tests. Mechanical behavior and self-heating of PA6 during necking are predicted well.